Morphometry of Kacang and Ettawa Crossbreed Goats Raised in Bali - I Nyoman Suyasa; I Wayan Suardana; I Gusti Agung Arta Putra; Ni Nyoman Suryani (Institute for Research and Community Service, Udayana University, 2022)
The consumption of animal protein from goats in Bali continues to increase every year. The supply level is not adequate with the level of demand, prompting the local government of Bali to improve the development of goats farmer in several areas of Bali. So far, the data on the morphometry of Kacang and the Ettawa crossbreed goats as the main supplier of lamb in Bali has not been found. Based on these considerations, this study is interesting to present. Observations on goat morphometry were carried out by measuring body length, head width, head height, chest width, chest depth, wither height, chest girth, and body length. The results of the observations were then analyzed by SPSS 25 program. The data of the study showed that the morphometry of Kacang and Ettawa crossbreed goats were almost different (P<0.01) in all parameters except the head width, chest width, and tail width. On the other hand, the morphometric of both Kacang and Ethawah crossbreed goats showed larger than another that raised out of Bali. This genetic resource must be maintained at its potential from decreasing quality in the future.